2020
DOI: 10.3389/fpls.2019.01696
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia and Ammonium Exposure of Basil (Ocimum basilicum L.) Growing in an Organically Fertilized Peat Substrate and Strategies to Mitigate Related Harmful Impacts on Plant Growth

Abstract: Organic pot-based production of basil (Ocimum basilicum L.) often has lower biomass yield than conventional cultivation. Previous investigations indicate that this growth impairment is related to high ammonium (NH 4 + ) concentrations in the growing media released by the mineralization of organic nitrogen (N) fertilizers. However, as a result of this ammonification process substrate pH may also increase. Under neutral to alkaline conditions NH 4 + is converted to ammonia (NH 3 ), which is known to be phytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Thus, complete stockpiling, as recommended by Heuberger et al [27], is quite risky. Furthermore, in the case of missing nitrification, ammonium-N will accumulate, damaging plants [68]. However, in the current research-except for the OPF-nitrification already started within the first week of incubation.…”
Section: Nitrogen Releasementioning
confidence: 57%
“…Thus, complete stockpiling, as recommended by Heuberger et al [27], is quite risky. Furthermore, in the case of missing nitrification, ammonium-N will accumulate, damaging plants [68]. However, in the current research-except for the OPF-nitrification already started within the first week of incubation.…”
Section: Nitrogen Releasementioning
confidence: 57%
“…The N-NO 3 reduction rate is lower, in the case of all experimental variants, compared to N-NH 4 and N-NO 2 ( Figure 25 , Figure 26 and Figure 27 ). Thus, previous studies concluded that, in the case of basil, plant growth is improved by lower N-NH 4 exposure, as well as a faster supply of N-NO 3 as an N source [ 70 ]. In aquaponics systems, the crops GM plays a dual role, both as a biofilter, but also as a support media for promoting plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…An increased nitrogen supply resulted in increased shoot-root dry weight and shoot-root length ratios in perennial and annual plant species [32], which was found in the IAU plants with Humicacid Fiber-Substrate compared to the EAU plants (Table 3) and not in the basil in the standard substrate (Table 2). However, the NH 4 -N levels should not be higher than the NO 3 − levels because basil was identi ed as being sensitive to higher levels of NH 4 + [36] especially with contents higher than 250 mg/L of N as amino acids [37], which were not reached by HFS. The change in NO 2 -N was highest in the IAU as an effect of the higher stocking densities compared to the EAU, thus increasing nitri cation processes.…”
Section: Discussionmentioning
confidence: 99%